Analisis Kesulitan Siswa Dalam Menyelesaikan Soal-Soal Higher Order Thinking Skills - Mita Miranda Sitanggang; Edi Syahputra (Journal of Student Research, 2024)
This research aims to analyze students' difficulties in solving HOTS questions in terms of facts, concepts, operations and principles. The method used is qualitative research with a descriptive approach. This research was carried out by collecting data in the form of information obtained from research subjects. This research is intended to describe or express in words (qualitatively) the results of the analysis of students' difficulties in solving questions which are Higher Order Thinking Skills. The subjects of this research were class IX students of GKPI Padang Bulan Private Middle School, Medan. The instruments in this research were test and interview instruments, where students were given questions to work on, then the researcher recorded the results of the students' answers and took 6 students to be interviewed based on the high, medium and low group categories. The results of the research showed that in the high group students experienced difficulties with principles, in the medium group students experienced difficulties with operations and principles and in the low group students experienced difficulties with facts, concepts, operations and principles. This shows the conclusion that GKPI Padang Bulan Medan Private Middle School students experience difficulties in solving HOTS questions.